2014
DOI: 10.1101/gad.242404.114
|View full text |Cite
|
Sign up to set email alerts
|

A unique DNA entry gate serves for regulated loading of the eukaryotic replicative helicase MCM2–7 onto DNA

Abstract: The regulated loading of the replicative helicase minichromosome maintenance proteins 2-7 (MCM2-7) onto replication origins is a prerequisite for replication fork establishment and genomic stability. Origin recognition complex (ORC), Cdc6, and Cdt1 assemble two MCM2-7 hexamers into one double hexamer around dsDNA. Although the MCM2-7 hexamer can adopt a ring shape with a gap between Mcm2 and Mcm5, it is unknown which Mcm interface functions as the DNA entry gate during regulated helicase loading. Here, we esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 55 publications
5
108
0
Order By: Relevance
“…5D). Thus, our data show that Mcm2-7 loading must occur prior to double-hexamer formation, consistent with the finding that a single Mcm2-7 hexamer is loaded onto DNA during OCCM formation, although the first hexamer requires ORC-Cdc6 for stability (Sun et al 2013;Samel et al 2014). The Mcm2-7 double hexamer encircles dsDNA (Evrin et al 2009; (Fig.…”
Section: Function Of the Mcm2/5 Gate In The Mcm2-7 Double Hexamersupporting
confidence: 75%
See 1 more Smart Citation
“…5D). Thus, our data show that Mcm2-7 loading must occur prior to double-hexamer formation, consistent with the finding that a single Mcm2-7 hexamer is loaded onto DNA during OCCM formation, although the first hexamer requires ORC-Cdc6 for stability (Sun et al 2013;Samel et al 2014). The Mcm2-7 double hexamer encircles dsDNA (Evrin et al 2009; (Fig.…”
Section: Function Of the Mcm2/5 Gate In The Mcm2-7 Double Hexamersupporting
confidence: 75%
“…Indeed, a DNA entry gate between Mcm2 and Mcm5 has been identified that is essential for pre-RC formation Samel et al 2014). If Mcm2-7 double-hexamer loading is a concerted process, as suggested Yardimci and Walter 2014), then DNA insertion into both Mcm2-7 hexamers needs to be coordinated, requiring the Mcm2/5 gate of each hexamer to be aligned to promote simultaneous ring opening.…”
Section: Function Of the Mcm2/5 Gate In The Mcm2-7 Double Hexamermentioning
confidence: 99%
“…Intrinsic to this is the functional loading of the MCM helicase complex, which is believed to involve ring opening between MCM subunits 2 and 5. 10, 11 Exactly how this is achieved on chromatin, and rendered functional by accurate interaction with both template and accessory factors, is not fully understood even in yeast.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical evidence indicates that the gate-open Mcm2-7 conformation lacks helicase activity, while the gateclosed form retains activity (29). In vivo, the Mcm gate has two known functions: (i) to serve as an entry site for DNA loading during origin association (29) and (ii) to regulate DNA unwinding during G 1 /S.…”
mentioning
confidence: 99%